Can The Supervision, Discipline, And Competency Of Employees Affect The Performance Of Employees At The Darussalam Camat Office, Big Aceh District? - Handayani, Meutia; Devi, Rizkia; Ardian, Ardian; Farlian, Talbani (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2022)
This study aims to determine whether supervision, discipline, and employee competence can affect employee performance either partially or simultaneously at the Darussalam District Office of Big Aceh District. The samples used in this study were employees at the Darussalam District Office of Big Aceh District. This study uses a quantitative approach. The analytical method used is multiple linear regression analysis using Evies 12. The results show that partially supervision and discipline have no infuence on employee performance, while competence has an influence on employee performance. Simultaneously supervision, discipline and competence of employees influence the performance of the employees of the Darussalam Sub-District Office.